2022
DOI: 10.1038/s41586-022-05484-5
|View full text |Cite
|
Sign up to set email alerts
|

Social trauma engages lateral septum circuitry to occlude social reward

Abstract: In humans, traumatic social experiences can contribute to psychiatric disorders1. It is suggested that social trauma impairs brain reward function such that social behaviour is no longer rewarding, leading to severe social avoidance2,3. In rodents, the chronic social defeat stress (CSDS) model has been used to understand the neurobiology underlying stress susceptibility versus resilience following social trauma, yet little is known regarding its impact on social reward4,5. Here we show that, following CSDS, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 61 publications
8
45
0
Order By: Relevance
“…This approach also used a validated cellular manipulation that causally induces aggression, and it was performed under a behavioral condition that would otherwise not yield aggressive attack behavior (i.e., we used female social partners). Specifically, we expressed an excitatory DREADD (AAV-hsyn-DIO-hM3Dq) in the ESR1+ cells of ventromedial hypothalamus, since it has been shown that direct excitation of these cells induces aggressive behavior towards female mice (Deonaraine et al, 2020; Li et al, 2022; Takahashi et al ., 2017). Experiments were performed in the male F1 offspring of female CD1 strain mice crossed with ESR1-Cre male mice on a C57 strain background.…”
Section: Resultsmentioning
confidence: 99%
“…This approach also used a validated cellular manipulation that causally induces aggression, and it was performed under a behavioral condition that would otherwise not yield aggressive attack behavior (i.e., we used female social partners). Specifically, we expressed an excitatory DREADD (AAV-hsyn-DIO-hM3Dq) in the ESR1+ cells of ventromedial hypothalamus, since it has been shown that direct excitation of these cells induces aggressive behavior towards female mice (Deonaraine et al, 2020; Li et al, 2022; Takahashi et al ., 2017). Experiments were performed in the male F1 offspring of female CD1 strain mice crossed with ESR1-Cre male mice on a C57 strain background.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, female mice companionship was given as a social and sexual reward during 21 days of chronic social defeat stress and confirmed the effect of this reward on chronic social defeat stress during sustained stress. The reward used in this study contains both social and sexual reward, in which the social reward is moreand sexual reward is less ( 60 ). However, in clinic, human beings are more social with more social constraints (e.g., ethical).…”
Section: Discussionmentioning
confidence: 99%
“…However, attributing particular aspects of behavioral control to distinct LS neuronal subpopulations has been challenging due to the incomplete understanding of LS neuronal diversity. Recent studies have focused on several molecularly defined groups of LS neurons to establish their involvement in social behavior 37,38 or context-specific defensive responses 16,17,39,40 . Our research complements these efforts, using a mouse model where Crhr2 -expressing Nkx2.1 -lineage neurons are absent from the lateral septum to assess the role of this subpopulation in the control of innate behavioral responses to stress-related stimuli.…”
Section: Discussionmentioning
confidence: 99%